(untitled) (World Bulletin of Public Health, 2022)
Echinococcosis is a disease developing as a result of penetration into the human body and development in it of the larval stage of the tapeworm echinococcus. Analysis of literature data and current clinical practice indicates an increase in the incidence of hepatic echinococcosis, expansion of endemic regions and more frequent cases of infection in non-endemic areas. An increase in the number of complicated forms of the liver echinococcosis has been registered during the last 20 years, their frequency reaches 84,6%. Relapses are observed in 54% of cases. This situation is due to the deterioration of sanitary and epidemiological control and clinical examination in the endemic areas, increased migration of the population, which has led to the aggravation of the problem of diagnostics and surgical treatment of echinococcosis in the CIS countries